Konsep Perawi Al-Sahabah dan Perbahasan di Sekitarnya - Hj. Sulaiman, Ishak (Jurnal Usuluddin, 1997)
Al-Sahabah has constantly become a controversial issue. In the actual fact, this comes out as result of imperfect conception of the concept itself especially when discussing it in terms of Hadith. The article is an attempt to elaborate systematically as it has been discussed by the authorities of Hadith.